Pengembangan Keterampilan Digital dan Kreativitas Pemasaran melalui Affiliate Marketing - Rahman, Habib Fatkhur; Aditiansyah, Mohammad Abim; Ariyanti, Meika Putri; Fitriyanti, Nafna; Azizah, Binti Khotimatul; Ayodhea, Regita Sheanon; Nisa, Siti Khoirun; Nisa, Alfiatun; Sari, Indri Duhita; Andaryuni, Fitri; Sa'diyah, Nur Halimatus; Sa'diyah, Halimatus; Mauludin, Moch. Syahrul Mauludin; Sulistyaningsih, Dewi; Mekarsari, Nadhifah Dyah; Khitam, Muhamad Akhsanul; Arini, Erni Zulfa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service program aims to improve the digital literacy and marketing skills of the Jatirejo Village community through affiliate marketing training, using the Participatory Action Research(PAR) method. This method was chosen because it actively involves the community in every stage of the program, including problem identification, planning, implementation, and evaluation, ensuring that the solutions are contextually relevant. The training focused on introducing the basic concepts of affiliate marketing, creating accounts on affiliate platforms, selecting appropriate products, and developing promotional content on social media. In addition, participants were equipped with technical skills such as product photography and persuasive copywriting, enabling them to adopt content-based marketing strategies aligned with current digital trends. The results showed a significant improvement in participants’ conceptual understanding, technical skills, and creativity in promoting local products. Positive impacts were also evident in the form of new income opportunities without requiring large capital and increased economic empowerment in the village. Despite challenges such as limited internet access and consistency in practice, recommendations including the establishment of a village affiliate marketer community, government support, and continuous training were proposed to overcome them. Therefore, this program represents a strategic step in strengthening the competitiveness of Jatirejo Village in the digital era.